Toxicity Effect of Mercury Chloride (HgCl2) on the Freshwater Gastropod, Indoplanorbis exustus - P.N. Mahale, H. Z. Patil* and (Journal of Ecobiotechnology, 2010)
Toxicity of HgCl2 was studied in immature & mature Indoplanorbis exustus snails exposed to different concentrationÂ  for a period of 24,48,72 & 96 hours. LC 50 values were 0.617, 0.422, 0.327, 0.275 ppm in immature snails & 0.501, 0.335, 0.237, 0.199 ppm in mature snails for 24, 48, 72 96 hours respectively.